Engineering validation for lithium target facility of the IFMIF under IFMIF/EVEDA project. (December 2016) - Wakai, E.; Kanemura, T.; Kondo, H.; Hirakawa, Y.; Ito, Y.; Serizawa, H.; Kawahito, Y.; Higashi, T.; Suzuki, A.; Fukada, S.; Furuya, K.; Esaki, K.; et al.
Highlights: The major progress of engineering validation activities in the IFMIF/EVEDA project joined by Japan and the EU was a verification of long-term stability of high-speed liquid lithium target flowing for fusion neutron source. Successful completion and achievement exceeding the goal of the full scale test of the high-speed liquid lithium flow for the fusion neutron source under the Broader Approach Activities aiming at the early realization of fusion energy jointly developed by Japan and the EU. The verification of the long-term stability of over the 1300 h high-speed liquid lithium target flow beyond the goal of 1000 h, using the test facility having the world's highest flow rate, and the verification of lithium purification and safety and the remote handling technique using fiber laser for the welding and cutting of the pipes were also performed. Abstract: The International Fusion Materials Irradiation Facility (IFMIF), presently in the Engineering Validation and Engineering Design Activities (EVEDA) phase was started from 2007 under the frame of the Broader Approach (BA) agreement. In the activities, a prototype Li loop with the world's highest flow rate of 3000 L/min was constructed in 2010, and it succeeded in generating a 100 mm wide and 25 mm thick with a free-surface lithium flow along a concave back plate steadily at a high-speed of 15 m/s at 250 °C for 1300 h. In the demonstration operation it was needed to develop the Li flowing measurement system with precious resolution less than 0.1 mm, and a new wave height measuring method which is laser-probe method was developed for measurements of the 3D geometry of the liquid Li target surface. Using the device, the stability of the variation in the Li flowing thickness which is required in the IFMIF specification was ± 1 mm or less as the liquid Li target, and the result was satisfied with it and the feasibility of the long-term stable liquid Li flow was also verified. The results of the other engineering validation tests such as lithium purification tests of lithium target facility have also been evaluated and summarized.